Special histological subtypes of breast cancer in a Hispanic Latino population - Gonzalo Ziegler Rodriguez; Gabriel De la Cruz Ku; Alanna Hickey; Sarah Roberts; Sheila Katherine Diaz-Mora; Augusto Ordonez; Luis Piedra Delgado; Jiddu Guart; Juan Haro Varas; Jorge Dunstan Yataco; Jose Manuel Cotrina Concha (PLoS ONE, 2025)
Introduction Special histologic subtypes of breast cancer have a unique biological behavior and outcomes. The literature has demonstrated that histologic and phenotype subclassification of breast cancer varies according to race and populations. Our aim was to describe the clinicopathological characteristics and outcomes of breast cancer with special histological subtypes in a Latin/Hispanic population. Methods A retrospective study was conducted. We reviewed the medical records of patients newly diagnosed with special histological subtypes of breast cancer at a single tertiary reference cancer center in Peru from 2014 to 2019. Results A total of 479 patients were included, the median age at diagnosis was 55 years (range 26–89). The majority of patients were from a metropolitan area (59.1%). The most common histological subtype was lobular (34.9%), followed by mucinous (12.7%), papillary (12.5%), apocrine (6.9%), metaplastic (5.4%), medullary (3.8%), cribriform (3.3%), neuroendocrine (0.8%), and 9.2% mixed histology. 61.6% had a moderately differentiated grade. The most common phenotype at diagnosis was HR + HER2- (57.7%), followed by triple-negative breast cancer (TNBC)(13.2%), showing a similar pattern after neoadjuvant therapy (NAT); HR + HER- (61.7%), and TNBC (16.3%). At diagnosis most patients were stage T2 (40.3%), N0 (61.0%) and stage II (40.7%); while after NAT, stage I (64.7%) was the most common. In regard to NAT, 45.9% received chemotherapy, 31.5% hormone therapy, 15.7% trastuzumab, and 5.8% radiotherapy. The majority underwent mastectomy (71.4%). In relation to adjuvant treatment, 72.7% received chemotherapy, 74.1% hormone therapy, 9.4% trastuzumab, and 76.4% radiotherapy. Loco-regional and distant recurrence occurred in 4.2% and 12.7%, respectively. With a median follow-up of 97 months (8 years), the overall survival (OS) at 5 years was 82%, with patients with cribriform histology presenting the best rate (100%) compared to the worst observed in patients with metaplastic histology (54%). Conclusions The most frequent special histologic subtypes of breast cancer in Latino-Hispanic patients were lobular, mucinous, papillary, metaplastic, and apocrine carcinomas. Patients were diagnosed at more advanced stages and more frequently presented a TNBC phenotype compared to the non-Hispanic White population. Certain histological subtypes in our population presented worse OS rates.